RI 5811 Volatilization Of Tin Chlorides From Bolivian Low-Grade Ores And Concentrates ? Summary - K. K. Kershner (The National Institute for Occupational Safety and Health (NIOSH), 1961)
The purpose of this research by the Federal Bureau of Mines was to investigate the recovery of tin from mine-run ores and low-grade concentrates. Over 95 percent of the total tin in such materials was volatilized to tin chlorides at temperatures ranging from 520° to 565° C. Gaseous mixtures of hydrogen and hydrogen chloride were used for reducing cassiterite to stannous oxide and for converting this compound to tin chlorides. The chlorides were swept from the reaction zone of an oscillating kiln by a rapid flow of reactant gases and collected in a condensing system. Losses of tin that occur in current metallurgical processing were prevented. Approximately the same time of treatment was required for minus 35-mesh mine-run ores and low-grade concentrates. In a continuous process, the circulating gases would require some enrichment.